Tenório de Albuquerque: a Brazilian in the Third Reich (1936-1937) - Marcelo Alves de Paula Lima (Iberoamericana. América Latina - España - Portugal, 2019)
This paper aims at analyzing the ideas of Arcy Tenório de Albuquerque, an ideologue and militant of the Brazilian Integralist Action, a fascist-inspired political party founded in 1932. Our sources were two books written by the author: one in 1936 and the other in 1937. Such books, pervaded by anti-Semitism and nationalism, contain the author’s impressions of his trip to Nazi Germany in 1936, as well as his opinions on Hitler, Nazism and Jews. The author states that his experience in Germany made him join the integralist movement when he went back to Brazil. Tenório regarded the Third Reich as a symbol of peace, progress and prosperity, claiming that Brazil needed something like Nazism.